Dynamic Evaluation and Prediction of Ecological Carrying Capacity of Water Resources in Tarim River Basin - ZHU Xueying; HUANG Shengzhi; HUANG Qiang; ZHENG Xudong; ZHANG Shaoqing; GAO Yuejiao (Renmin Zhujiang)
An ecological footprint model of water resources is used to evaluate the the evolution of per capita ecological footprint of water resources,ecological carrying capacity,ecological profit and loss,and ecological carrying status from 2005 to 2020 in the Tarim River Basin,and a gray prediction model is used to forecast the ecological surplus/deficit from 2021 to 2030.The results indicate that the water resources in the Tarim River Basin as a whole are in a state of ecological deficit,and the ecological pressure index of water resources in most regions is greater than 1.0.Ecological overload is serious;the ecological footprint of water resources per 10 000 yuan GDP continues to decline,while the load index of water resources is on the rise.In the future,the deficit of water resources in the Tahe River Basin will show a downward trend year by year.The research results can effectively serve the ecological environment protection and planning and management of water resources in the Tahe River Basin.